EFFECT OF AUDIT DELAY, AUDIT QUALITY AND LEVERAGE AGAINST FINANCIAL REPORTING FRAUD: AUDITOR SWITCHING AS A VARIABLE - Chairian Tomy; Arfan Ikhsan; Andri Zainal (Jurnal Ilmiah Teunuleh, 2022)
This study aims to show the influence of variable audit delays, audit quality and leverage, on financial reporting fraud: auditor switching as intervening variables on idX-listed property, real estate, and building construction companies. The population of this study is 85 companies, by accessing financial statements and auditor reports through the Indonesia Stock Exchange website. The sampling method used is the purposive sampling method, so 30 sample companies were obtained for 3 years of observation (2018-2020) with 90 units of analysis. The data analysis method used is the logistic regression method. Based on the results of data processing using the logistic regression method with SPSS software, it is known that simultaneous audit delays, audit quality and levarage have a significant influence on auditor switching at a significance level of 5%. Similarly, the influence that occurs between switching audiors on financial reporting fraud is statistically significant at a significance level of 5%. Switching auditors are also able to mediate the relationship between audit delay, audit quality and leverage against financial reporting fraud with a significance level of 5%.